Lesson Study with Positive Reinforcement Techniques: Its Impact on Resilience and Learning Motivation - Dewi, Widya Novi Angga; Sari, Dwi Septiana (Psikopedagogia, 2023)
Resilience and motivation to learn are crucial aspects that must be developed in students. However, there is a need to enhance resilience and motivation to learn in statistics courses. This research aims to determine the impact of lesson study using positive reinforcement techniques on increasing resilience and learning motivation in statistics courses. This experimental research employs a one-group pretest-posttest design. The study involved 47 first-semester students from the Counseling Guidance Study Program at Ivet University for the 2022/2023 academic year, who were randomly selected using simple random sampling. The research utilized a resilience and learning motivation scale. Pretest and posttest scores were analyzed using t-test statistics. The results show a significant influence (p-value 0.000) on resilience and learning motivation, leading to the rejection of the null hypothesis. Therefore, the research concludes that lesson study using positive reinforcement techniques effectively increases the resilience and learning motivation of Counseling Guidance students who face difficulties in learning statistics. The findings of this research can serve as a reference to help enhance the resilience and learning motivation of guidance and counseling students.